29th annual conference of the European Society for Biomaterials. (6th December 2019) - Habibovic, Pamela; Hofmann, Sandra; van den Beucken, Jeroen
Abstract : Guest editors Pamela Habibovic, Sandra Hofmann and Jeroen van den Beucken introduce this themed collection on behalf of the European Society for Biomaterials, showcasing research presented at the 29th Annual Meeting of the European Society for Biomaterials, Maastricht, 2018.